Let's Get Writing! - Browning, Elizabeth; DeVries, Kirsten; Boylan, Kathy; Kurtz, Jenifer; Burton, Katelyn (Open textbook library., 2018)
This introduction is designed to exemplify how writers think about and produce text. The guiding features are the following: Every good piece of writing is an argument. Everything worth writing and reading begins with a specific question. Improving skills takes practice, feedback, and re-thinking, redoing, revising. The layout of our book implies there is a beginning, middle, and end to a writing course, but because writing is both an art and a skill, people will find their own processes for learning, improving, and using these skills. Writing processes differ because we are each looking for a workable schemata that fits our way of thinking. Try out a variety of writing processes and strategies, and find what works for you. If you are not uncomfortable on this journey, you simply are not stretching yet. Learning is prickly, awkward, and risky, so if it does not feel a bit unnerving, push harder and farther.